An unexpected Amish proposal - Good, Rachel J. (Good, Rachel J. Surprised by love., 2021)
When her childhood crush -Gideon Hartzler-comes to the aid of her family, offering her a new place to sell her baked goods, Fern Blauch tries to deny the growing attraction between them due to the many obstacles that stand in their way.